Family and Gender among American Muslims - Juliane Hammer (International Institute of Islamic Thought, 2000)
Family and Gender among American Muslims presents a multitude of theoretical and empirical discussions about the issues of family and gender in various American Muslim communities. Divided into three main sections, the first section, "Values, Structure, and Variations in Muslim Families" presents articles based on empirical research on issues such as the role of women in an Iranian ethnic economy, the selfevaluation of Palestinian women's lives, the issue of mut'a-marriage among Lebanese Shi'as, and the problems of South Asian Muslim families in the United States. The second section, "Practical Issues for Families,'' provides insight into health issues, the work of an Arab-American community center, care for the elderly and problems of second-generation Arabs with marriage and role conflicts. The third section presents an interesting account of five Muslim immigrants, as narrated by them. The book is an insightful introduction into some of the problems faced by American Mu Jim immigrants and their children on a daily basis. The questions of how to preserve an ethnic and religious identity in a society that has different values and mies is central to the lives of these American Muslims. It is a recurring theme running throughout most articles and illustrated in different ways. Some of the authors highlight problems and make recommendations to parents, community leaders, teachers, and social workers on how to solve these problems. The first article by Yvonne Y. Haddad and Jane I. Smith gives an overview of the important topics concerning Islamic values and the questions of gender, such as dating, marriage, women and work, birth control, raising of children, and the observation of American holidays. The authors present a realistic ...